Strategi Multibahasa dan Kegunaan Alih Kode dan Campur Kode Lagu Jepang Boyband Korea Seventeen - Ridesta, Vitara (P3M Politeknik Negeri Media Kreatif, 2025)
This study evaluates the use of code-switching and code-mixing in Japanese-language songs popularized by the Korean boyband Seventeen as part of the multilingual functions in pop music media. Using a qualitative approach, this analysis applies Poplack and Gumperz's code-switching theories regarding bilingualism phenomena, as well as Edwin and Even’s code-mixing theory in the context of World Englishes. Data were collected through documentation and transcription of song lyrics, focusing on the linguistic classification of code-switching and code-mixing. The study reveals that the use of code-switching serves complex communicative functions, not limited to two-way interaction, but also as a strategy for message delivery in one-way communication, such as in songs. These findings broaden the understanding of the function of code-switching in one-way communication contexts and underscore the important role of multilingualism in expanding a song’s global reach while reinforcing the linguistic identity of the artist.